HUBUNGAN ANTARA PENGETAHUAN, KECEMASAN, FAKTOR SOSIAL DENGAN INTENSITAS ANC DI MASA PANDEMI COVID-19 DI PMB LILIS SURYAWATI JOMBANG - Ratna Dewi Permatasari; Any Isro'aini (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2022)
Pregnancy is the most risky period for psychological disorders for the mothers, especially during the COVID-19 pandemic. Where it can be a risk factor that affects the increase in high-risk pregnancies. The lack of knowledge, as well as the lack of support from the family adds to the anxiety of pregnant women which has an impact on ANC visits by pregnant women. The purpose of this study was to determine the relationship between knowledge, anxiety, social factors (family support) on the intensity of ANC visits to pregnant women during the Covid-19 pandemic at PMB Ny. L Sambong Dukuh Jombang. The research method used quantitative research with a cross sectional research design. The sampling technique was a total sampling of 55 pregnant women in the third trimester. Statistical test was carried out using the Pearson Correlation test and the result showed that the p value of knowledge (p = 0.027), anxiety (p = 0.048), social factors (p = 0.038) where p value 0.05 means H0 was accepted or there was a relationship between knowledge, anxiety, social factors / family support with the intensity of ANC in pregnant women during the covid-19 pandemic Conclusion: there was a relationship between knowledge, anxiety, social factors and the intensity of ANC in pregnant women during the Covid-19 pandemic. Keywords: Knowledge, Anxiety, Social Factors, Intensity of ANC